Integrative analyses of metabolome and transcriptome reveal the dynamic accumulation and regulatory network in rhizomes and fruits of Polygonatum cyrtonema Hua - Luyun Ning; Yuanshu Xu; Lu Luo; Limin Gong; Yeman Liu; Zhi Wang; Wei Wang (BMC Genomics, 2024)
Abstract Background According to Chinese ancient books, both fruits and rhizomes of Polygonatum cyrtonema Hua have medicinal and edible values. Up to now, there is no report about the metabolite profiles and regulatory network in fruits and different year-old rhizomes of P. cyrtonema. Results In this study, we performed integrative analyses of metabolome and transcriptome to reveal the dynamic accumulation and regulatory network of fruits and different year-old rhizomes in P. cyrtonema. The relative content of phenolic acids, lignans and coumarins, flavonoids and alkaloids increased with growth years, while steroids and lipids decreased with it. In addition, the relative content of nucleotides and derivatives, flavonoids, organic acids, steroids and lipids in fruits were higher than rhizomes. Genes that might relate to the biosynthesis of polysaccharides, flavonoids, triterpene saponins and alkaloids biosynthesis were further analyzed by transcriptome analysis, including sacA, GMPP, PMM, CCoAOMT, CHI, ANR, CHS, DXS, GGPS, ZEP, CYP72A219 and so on, for their expressions were positively correlated with the relative content of the metabolites. Additionally, the correlation network in sugar and aromatic amino acids metabolites were constructed to further illustrate the biosynthesis of polysaccharides, flavonoids and alkaloids in P. cyrtonema, and some transcription factors (TFs) were screened, such as C2C2, MYB, bZIP, GRAS and NAC. Conclusions This study can deepen our understanding of the accumulation patterns and molecular mechanism of the main compounds in P. cyrtonema, and provide reference for the standardize production of P. cyrtonema.